BizTalk 2006 Recipes - Beckner, Mark (Apress, 2012)
Enterprise integration is a complex problem. Even with an exceptional product like BizTalk Server 2006, many variables and considerations contribute to the enterprise integration puzzle. Each of this book’s authors has worked with BizTalk since the product’s inception in the early 2000s and has implemented more than ten enterprise integration projects during his IT professional consultant career. Many books on the market provide solutions without context to the problem. BizTalk 2006 Recipes: A Problem-Solution Approach aims to not only give the reader solutions to common BizTalk integration scenarios, but also to provide the reader with information related to the problem at hand. By handpicking the key scenarios, we hope to arm the reader with sufficient information to make the best decision when faced with enterprise integration challenges.